Islamic Ethics in Personal and Social Life - Putra Muallimin; Inayatillah Inayatillah (Global Education Journal, 2026)
This research aims to examine the concept and implementation of Islamic ethics in personal and social life based on the latest scientific literature review. The method used is library research with a descriptive-analytical approach, through the analysis of primary sources in the form of the Qur'an and Hadith as well as secondary sources such as journals and academic books. The results of the study show that Islamic ethics is a theocentric and comprehensive value system, including human relations with God (ḥabl min Allāh) and human relations with others (ḥabl min al-nās). In personal life, Islamic ethics play a role in shaping individual character through the internalization of values such as honesty, trust, patience, and responsibility. Meanwhile, in social life, Islamic ethics function as a guideline in creating harmonious interactions through the principles of justice, tolerance, and help. This research also found that technological developments and globalization are challenges in the application of Islamic ethics, especially in the context of digital communication. Therefore, strengthening strategies through education, family roles, digital literacy, and contextual approaches are needed so that Islamic ethical values remain relevant and applicable in modern life.